Strategic Appraisal The Changing Role of Information in Warfare - Khalilzad, Zalmay (RAND Corporation, 1999)
Advances in information technology have led us to rely on easy communication and readily available information--both in our personal lives and in the life of our nation. For the most part, we have rightly welcomed these changes. But information that is readily available is available to friend and foe alike; a system that relies on communication can become useless if its ability to communicate is interfered with or destroyed. Because this reliance is so general, attacks on the information infrastructure can have widespread effects, both for the military and for society. And such attacks can come from a variety of sources, some difficult or impossible to identify. This, the third volume in the Strategic Appraisal series, draws on the expertise of researchers from across RAND to explore the opportunities and vulnerabilities inherent in the increasing reliance on information technology, looking both at its usefulness to the warrior and the need to protect its usefulness for everyone. The Strategic Appraisal series is intended to review, for a broad audience, issues bearing on national security and defense planning.